Dampak Penggunaan Artificial Intelligence Terhadap Peran Pendidik Sekolah Dasar di Era Merdeka Belajar - Ikhtiatus Sholihah; Sulton Akbar; Agung Setyawan (LLDIKTI WILAYAH XIII, 2026)
This study examines how artificial intelligence affects the role of elementary school educators in Indonesia within the framework of the Freedom of Learning paradigm. This study synthesizes findings from leading books, national and international journals, conference proceedings, and official education policy documents related to the use of artificial intelligence in elementary education using qualitative literature research methods. According to the findings, educators face both great opportunities and difficulties as a result of artificial intelligence. Some of the benefits of using artificial intelligence include increased administrative efficiency, support for personalized and adaptive learning, real-time feedback that frees educators to focus more on character education and the social-emotional growth of students, and increased accessibility to education, especially for students with disabilities or geographical limitations. However, there are also several challenges, such as the lack of readiness and knowledge of educators regarding the adoption of artificial intelligence in learning, the dependence of educators on technology, concerns about the replacement of the teaching profession by artificial intelligence, and unequal access to digital infrastructure, especially in rural areas. These results highlight the need for artificial intelligence to function as a collaborative and supportive tool that reinforces, rather than replaces, the moral and humanistic aspects of education. To ensure that educators can successfully and ethically integrate artificial intelligence while maintaining the core principles of human-centered education in the digital age, it is essential for them to receive professional development and ongoing training in digital literacy.